Keabsahan Pengelolaan Destinasi Pariwisata Kota Tual Ditinjau Dari Undang-Undang Nomor 10 Tahun 2009 Tentang Kepariwisataan - Nurul Fatiha Renuat; Julista Mustamu; Merlien Irene Matitaputty (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Tual City as an autonomous region that has regional tourism potential currently cannot be managed optimally by the regional government and regional apparatus in this case the tourism office.Purposes of the Research: The purpose of this study is to find out and analyze tourism destination managers who are carried out without being based on the Master Design for Tourism Development and to find out and analyze the legal consequences of managing tourism destinations without being based on the Master Design for Tourism Development. Methods of the Research: This research is a normative research that refers to the legislation and legal materials related to the substance of the research, then linked to the main problems in this research. The approach taken in this research is a statutory approach and a conceptual approach.Results of the Research: The results of the research are that the first management of tourism destinations cannot be carried out without being based on the Master Design for Tourism Development because it is not based on the Regional Tourism Development Master Plan (RIPPARDA) as a special regulation governing tourism and the second result is that the main legal consequence is that no budget is disbursed. to the local government and related devices because the requirement for a regional budget is the existence of the Regional Tourism Development Master Plan (RIPPARDA) so that tourism management in Tual City automatically becomes hampered and cannot run optimally.